2007
DOI: 10.2174/092986707781368540
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary Diseases and Insulin Resistance

Abstract: In recent years, there has been an increasing prevalence of obesity and related diseases. This epidemiological change has increased the interest of researchers in the molecular and biochemical pathways involved in the pathogenesis of hepatic and biliary diseases. Insulin resistance is considered the major mechanism involved in the hepatic and biliary manifestations of obesity. Epidemiological, clinical, and basic research demonstrates that insulin resistance is associated with gallstone disease, nonalcoholic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 118 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…Also, liver steatosis was more pronounced in the olive oil-treated animals, as indicated by the increase in organ weight and triglyceride content. An increase in the hepatic synthesis and production of triglycerides is frequently associated with insulin resistance and obesity in humans [32]. The olive oil-fed animals also showed insulin resistance in adipose tissue, at variance with those fed corn oil, and a tendency towards increased insulin plasma levels.…”
Section: Discussionmentioning
confidence: 96%
“…Also, liver steatosis was more pronounced in the olive oil-treated animals, as indicated by the increase in organ weight and triglyceride content. An increase in the hepatic synthesis and production of triglycerides is frequently associated with insulin resistance and obesity in humans [32]. The olive oil-fed animals also showed insulin resistance in adipose tissue, at variance with those fed corn oil, and a tendency towards increased insulin plasma levels.…”
Section: Discussionmentioning
confidence: 96%
“…[35][36][37] In a recent study, a prevalence of gallstones of 2% was found by ultrasound in asymptomatic obese children and adolescents between 8 and 18 years of age (eight girls and two boys over 493 subjects), all of whom were postpubertal. 6 The link between obesity and the risk of gallbladder disease seems to be secondary, at least in part, to insulin resistance, 38 a mechanism also most likely involving increased serum levels of leptin 39 and increased hepatic secretion of cholesterol. 8 Our results found the presence of a distinctive gallbladder hypomotility in adult obese.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Di Ciaula et al ., 32 the authors demonstrated gallbladder and gastric motility defects were associated with obesity in preadolescents and adults. The link between obesity and the risk of gallbladder disease seems to be secondary, at least in part, to insulin resistance, 33 a mechanism also most likely involving increased serum levels of leptin 34 and increased hepatic secretion of cholesterol.…”
Section: Discussionmentioning
confidence: 99%